PENDIDIKAN ANTIKORUPSI DI INDONESIA - -, Supriyanta - (Universitas Slamet Riyadi, 2012)
Abstract: Education should be able to transform the moral values, education also serves to'social engineering in order to build an effective social capital. Internalization thevalues of religion and anti-corruption more specifically, be able to contribute to themental and moral development of a clean and honest. Moreover anti-corruptioneducation should not just stop at the level of education but should strive to be amovement that involves various elements of society.Keywords:anti-corruption education